Investigation of in vivo cardiac chambers composite rendering / Muhammad Abdullah Adli Ahmad Kamal - Muhammad Abdullah Adli, Ahmad Kamal (2021)
Heart disease is the most common cause of death in the world annually. Many fatalities can be avoided if the anomalies in the condition of the heart can be detected earlier for which proper treatment and preventive action can be taken. Detection of this anomalies can be done noninvasively through medical imaging modalities such as by using Computed Tomography (CT) scan. However, accurate interpretation of the heart using 2D images are often hard to do as it is visualized on a flat plane. Therefore, it is important to have a clear representation of the heart using a 3D model which would enable a more accurate interpretation of the heart and its inner chamber to be done for the detection of any anomalies. A 3D model reconstructed through the VTK program software using layers of 2D CT scan images are therefore proposed for this purpose. In this study, 399 layers of 2D CT scan image was used for the 3D model reconstruction. As a comparison, another 3D model was also reconstructed with the same 2D CT scan images using another software, 3D slicer. Although both software is able to reconstruct a good model of the heart, VTK appears to be the superior option for investigating the inner chambers of the heart. Both software also allows the measurement of the length between two points which enables the length of object under investigation to be estimated. In conclusion, VTK is able to reconstruct a good 3-dimensional representation of the heart which helps medical practitioners to better detect anomalies in their patients.